Lighting up the dark: Liquidity in the German corporate bond market - Yalin Gündüz; Giorgio Ottonello; Loriana Pelizzon; Michael Schneider; Marti G. Subrahmanyam (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We study the impact of transparency on liquidity in OTC markets. We do so by providing an analysis of liquidity in a corporate bond market without trade transparency (Germany), and comparing our findings to a market with full post-trade disclosure (the U.S.). We employ a unique regulatory dataset of transactions of German financial institutions from 2008 until 2014 to find that: First, overall trading activity is much lower in the German market than in the U.S. Second, similar to the U.S., the determinants of German corporate bond liquidity are in line with search theories of OTC markets. Third, surprisingly, frequently traded German bonds have transaction costs that are 39-61 bp lower than a matched sample of bonds in the U.S. Our results support the notion that, while market liquidity is generally higher in transparent markets, a sub-set of bonds could be more liquid in more opaque markets because of investors "crowding" their demand into a small number of more actively traded securities.
Keywords: G15; 330; Corporate Bonds; WpHG; Liquidity; Transparency; OTC markets